The Deepening of the Digital Divide in the Czech Republic - Petr Lupáč; Jan Sládek (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2008)
In their paper, the authors question the contemporary state of the digital divide in the Czech Republic. The description is structured according to the model of successive access elaborated by Jan van Dijk; data for analysis are taken from the available relevant sources, namely from the Czech branch of the World Internet Project, Czech Statistical Office reports, and the Information Literacy Research commissioned by the Czech Ministry of Informatics. Their basic hypothesis is that the digital divide is deepening in the Czech Republic; the basic outcome of the article is the summary of the most evident reasons for the deepening divide hypothesis and recommendations for future research in the area.